2014 IEEE Symposium on Computational Intelligence in Production and Logistics Systems (CIPLS) 2014
DOI: 10.1109/cipls.2014.7007162
|View full text |Cite
|
Sign up to set email alerts
|

An improved optimization method based on the intelligent water drops algorithm for the vehicle routing problem

Abstract: We introduce an improved intelligent water drops (IIWD) algorithm as a new swarm-based nature inspired algorithm to solve capacitated vehicle routing problem. IIWD algorithm introduces new adjustments and features that help to optimize the VRP problem with higher efficiency. We reinforce this algorithm to have satisfactory consequences in controlling the balance between diversification and intensification of the search process. We solve 14 well-known benchmark instances in the literature to compare the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The intelligent water drop algorithm has been applied in many natural sciences and engineering sciences, showing strong advantages and potential. Since then, the IWD algorithm has been applied to many combinatorial optimization problems, including TSP [26], multiple knapsack [27], vehicle routing [28], and job shop scheduling [29], and the results obtained are very satisfactory.…”
Section: Intelligent Water Drop Algorithmsmentioning
confidence: 99%
“…The intelligent water drop algorithm has been applied in many natural sciences and engineering sciences, showing strong advantages and potential. Since then, the IWD algorithm has been applied to many combinatorial optimization problems, including TSP [26], multiple knapsack [27], vehicle routing [28], and job shop scheduling [29], and the results obtained are very satisfactory.…”
Section: Intelligent Water Drop Algorithmsmentioning
confidence: 99%
“…Also, a cuckoo optimization algorithm was proposed to solve large scale problems that have no optimum solution. As future direction of research, one can apply Intelligent water drops (e.g., Booyavi et al, 2014) or Harmony search (e.g., Komaki et al, 2014) and compare them to the proposed COA in this study.…”
Section: Resultsmentioning
confidence: 98%
“…In this review, we have identified the algorithmic ideas proposed to improve IWD since its initial publication in 2007. A few articles seek to overcome drawbacks and limitation of the algorithm (Msallam and Hamdan, 2011;Alijla et al, 2014), while others propose modifications to enhance its exploration-exploitation capabilities (Duan et al, 2008(Duan et al, , 2009Niu et al, 2012;Booyavi et al, 2014;Teymourian et al, 2016a). Although the research on IWD is not particularly rich, we found that almost everything proposed to modify this algorithm consists of ideas that were first proposed in the context of ACO.…”
Section: Modifications Of Iwdmentioning
confidence: 95%
“…This is a relatively minor modification that, in the case of ACO, was already present in its very first formulation (Dorigo et al, 1991b). Later, Booyavi et al (2014) and Teymourian et al (2016b) have proposed the use of a parameter λ to weight the importance of soil with respect to heuristic information. Also this weighting mechanism is a part of most ACO algorithms and in particular was already present in the very first ones (Dorigo and Stützle, 2004).…”
Section: Modifications Of Iwdmentioning
confidence: 99%